The chronicles of Narnia. Prince Caspian - Johnson, Mark, 1945 December 27-; Adamson, Andrew; Steuer, Philip; Markus, Christopher; McFeely, Stephen; Henley, Georgie; Keynes, Skandar; Moseley, William, 1987-; Popplewell, Anna, 1988-; Barnes, Ben, 1981-; Dinklage, Peter; Favino, Pierfrancesco; et al. ([United States] : Walt Disney Home Entertainment ; Burbank, Calif. : Distributed by Buena Vista Home Entertainment, 2008)
The four Pevensie children - Peter, Susan, Edmund and Lucy - return to Narnia, only to discover that hundreds of years have passed since they ruled there. Now, crowning himself king, the evil General Miraz has taken charge. The children enlist the help of a heroic mouse called Reepicheep. They set out to find the exiled Prince Caspian, determined to see him rightfully named king.
Special features: disc 1. Widescreen version -- Audio commentary with director Andrew Adamson and actors -- Language: English Dolby digital 5.1 surround ; French Dolby digital 5.1 ; Spanish Dolby digital 5.1 -- Subtitles: English, French, Spanish.
DVD, widescreen; Dolby Digital 5.1 surround.
English (5.1 Dolby Digital), dubbed French (5.1 Dolby Digital) or dubbed Spanish (5.1 Dolby Digital) dialogue, French or Spanish subtitles; English subtitles for the hearing impaired.
Voices: Liam Neeson, Ken Stott, Harry Gregson-Williams, Sim Evan-Jones, David Walliams, Josh Campbell, Eddie Izzard.
Georgie Henley, Skandar Keynes, William Moseley, Anna Popplewell, Ben Barnes, Peter Dinklage, Pierfrancesco Favino, Vincent Grass, Sergio Castellitto.
Director of photography, Karl Walter Lindenlaub ; editors, Josh Campbell, Sim Evan-Jones ; music composed by Harry Gregson-Williams ; costume designer, Isis Mussenden ; production designer, Roger Ford ; lead animator, Philip Morris.
Based on the book by C.S. Lewis.
Keywords: Narnia (Imaginary place) -- Juvenile drama; Siblings -- Juvenile drama; Princes -- Juvenile drama; Good and evil -- Juvenile drama; Imaginary wars and battles -- Juvenile drama; Children's films; Narnia (Imaginary place) -- Drama; Siblings -- Drama; Princes -- Drama; Good and evil -- Drama; Imaginary wars and battles -- Drama; Narnia (Imaginary place) -- Drama; Siblings -- Drama; Princes -- Drama; Children's films; Fantasy films; Action and adventure films; Film adaptations; Children's films; Feature films; Fiction films; Video recordings for the hearing impaired; Fantasy films; Adventure films; Fantasy -- Feature; Adventure -- Feature